Credit Risk Management Practices and Perceived Challenges among Credit Cooperative Clients in the Philippines - Calub, Floresito D.; Sanchez, Judith J.; Montenegro, Donald L. (International Review of Management and Marketing, 2026)
Effective credit risk management is central to the sustainability of credit cooperatives, yet limited empirical research examines how these practices are experienced by clients. This study investigated credit risk management practices and perceived challenges among clients of selected credit cooperatives in Surigao del Sur, Philippines. Using a descriptive–correlational research design, survey data were collected from 339 clients selected through proportionate stratified sampling. Descriptive statistics, Spearman’s rho correlation, and multiple regression analyses were employed. Results showed a high level of implementation of client appraisal, credit risk control, and collection policy practices, alongside generally low levels of perceived challenges. Correlation analysis revealed differentiated relationships among variables, with client appraisal practices positively associated with perceived challenges, while credit risk control and collection policy practices were negatively associated with their corresponding challenges. Regression results further identified client appraisal practices as the only significant predictor of perceived challenges. These findings indicate that although credit cooperatives have largely institutionalized effective credit risk management systems, appraisal procedures remain the most perceptually demanding stage for clients. The study contributes to cooperative finance literature by emphasizing the importance of distinguishing between the technical effectiveness of credit risk management and its experiential impact on clients. The findings offer practical insights for cooperative managers and policymakers on refining appraisal processes while sustaining robust control and collection mechanisms to support inclusive, client-centered, and sustainable cooperative lending.